SLP Method Boosts Production Efficiency by 16% in Indonesia: Metode SLP Meningkatkan Efisiensi Produksi sebesar 16% di Indonesia - Kusuma , Dewi Fortuna; Cahyana , Atikha Sidhi (Indonesian Journal of Innovation Studies, 2024)
The study on improving the facility layout at CV. Surya Mega Yokasa demonstrated that the Systematic Layout Planning (SLP) method significantly enhances the efficiency of the production process, with a total reduction in material displacement distance by 13.45 meters and an efficiency increase of 16%. These findings imply that careful consideration of workflow and qualitative factors in layout planning can markedly optimize production flow and reduce congestion. However, the study did not factor in the Material Handling Costs (MHC), suggesting that future research should integrate MHC analysis to provide a more comprehensive evaluation of layout effectiveness and further optimize production efficiency. Highlight: Efficiency Boost: SLP reduced displacement by 13.45m, increasing efficiency by 16%. Improved Workflow: SLP method improved production flow, reducing congestion. Future Focus: Include Material Handling Costs for better layout evaluation. Keywoard: Systematic Layout Planning, Blocplan, Production Efficiency, Material Flow, Facility Layout